How did the internet communication media report on the outbreak the Guillain-Barre Syndrome in Peru? - Granados-Castañeda, Luciana Rocío (2021)
Objetive: Analyze the characteristics of the news about Guillain-Barré syndrome issued by the main web media in Peru, the outbreak during May to July 2018. Material and Methods: The characteristics of the news issued by the main media were analyzed. Peruvian web communication on the Guillain-Barré Syndrome between the months of May to July 2018. The news was classified according to the news (informative, educational and with high perception of the risk of contagion and death), scope, date and framing. Results: It was found that the highest percentage of news items were informative (25.7%), while those with the lowest percentage were those of an educational nature (7.8%). In the analysis of the frame it was found that the highest percentage of news focused on the case report of Guillain-Barré (56.4%), while the lowest percentage was the shortage of medicines (2.2%). Conclusions: Most of the news was informative about the cases of Guillain-Barre syndrome.